Testing lead-lag effect and cointegration between FTSE 100 Index and its futures - huang, lin (2008)
Abstract This dissertation conducted a literature review on three areas: cointegration theory, the development of empirical cointegration studies, lead-lag relationship in spot market indices and future markets, and the spot-future cointegration. In the section, various markets have been examined and different conclusions and explanations for the existence or the non-existence of lead-lag relationship are reviewed. Research methodology has been paid great attention in this dissertation. Three areas are covered in the section: model-building philosophies discusses various frames to approach modelling; the contrast and comparison of correlation and cointegration in terms of methodology; and the concrete modelling method adopted in this dissertation. In the following modelling steps section, both models are discussed in details for testing lead-lag effect and cointegration relationship. Data details are described in following section of data issues, before the modelling results are presented and discussed in the section of the results and analysis. The contribution of this dissertation is to use updated time series date to investigate a previously well examined phenomenon: the lead-lag relationship and its ECM representation in FTSE 100 Index and its futures. The main conclusion of this study is that there is no lead-lag relationship found using daily data of FTSE 100 Index and its futures. However, both the index and its future are cointegrated and future price at time t seems to affect the index price at time t but the opposite is not found. Rather, changes in future prices show a quite strong autoregressive property which may be the reflection of the high volatility of future market. The finding is consistent with previous financial literature.